2003
DOI: 10.2166/wp.2003.0026
|View full text |Cite
|
Sign up to set email alerts
|

The effects of irrigation on poverty: a framework for analysis

Abstract: Irrigation projects have been the subject of much bad press coverage because of the sometimes very damaging environmental and social impacts associated with large-scale projects such as dams, declining aid to agriculture and falling rates of economic returns to irrigation since the heyday of the 1970s. Yet irrigation remains one of the most crucial inputs into farming and therefore a potentially important poverty reduction tool for the 21st century. We review some of the evidence surrounding trends in investme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 8 publications
4
80
0
4
Order By: Relevance
“…514,8 con una significancia de 10%. Entonces, al menos en los distritos donde se asignó un mayor gasto en riego, se encuentra un efecto positivo en el VBP, posiblemente explicado por un incremento en el rendimiento (Lipton et al, 2003;Hussain y Hanjra, 2004). Asimismo, tanto para el efecto T50 como el T20 se incrementa el porcentaje del VBP cuyo destino es la venta, lo cual puede deberse a que, al contar con una oferta de agua más estable y segura, esto les permite elegir cultivos con una mayor demanda de mercado (Schoengold y Zilberman, 2007).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…514,8 con una significancia de 10%. Entonces, al menos en los distritos donde se asignó un mayor gasto en riego, se encuentra un efecto positivo en el VBP, posiblemente explicado por un incremento en el rendimiento (Lipton et al, 2003;Hussain y Hanjra, 2004). Asimismo, tanto para el efecto T50 como el T20 se incrementa el porcentaje del VBP cuyo destino es la venta, lo cual puede deberse a que, al contar con una oferta de agua más estable y segura, esto les permite elegir cultivos con una mayor demanda de mercado (Schoengold y Zilberman, 2007).…”
Section: Resultsunclassified
“…Sin embargo, como sostienen Lipton, Litchfield y Faurès (2003), su impacto será diferenciado por la gran heterogeneidad que existe dentro de la pobreza. Asimismo, tal como señalan Schoengold y Zilberman (2007), puede implicar costos como los ambientales debido a la destrucción de hábitats y bloqueo de corredores migratorios de especies, salinidad de fuentes de agua dulce, anegamiento y salinidad de la tierra, reducción de sedimento y nutrientes en el agua y su contaminación.…”
Section: Literatura Teórica Sobre El Efecto Del Riegounclassified
See 2 more Smart Citations
“…Despite questions raised on the performance of investments in irrigation in the past, there is evidence that investments in irrigated areas contributed to significant agricultural production growth, food security and poverty reduction in the target areas (De Fraiture et al, 2010;Fan et al, 2000;Huang et al, 2006;Lipton et al, 2003;Turral et al, 2010). For example, Domenech and Ringler (2013) reported that the impact of irrigation on yield can be as much as a 150% increase in maize and other crops in Africa, because the base yield levels are low.…”
Section: Importance Of Investments In Agricultural Water and Irrigatimentioning
confidence: 99%